Evaluating the relationship between tooth color and enamel thickness, using twin flash photography, cross‐polarization photography, and spectrophotometer. Issue 1 (11th December 2019) - He, Wei‐Hung; Park, Cheryl J.; Byun, Sangho; Tan, Daniel; Lin, Chih Y.; Chee, Winston
Abstract: Objectives: To understand (a) the effects of labial enamel on tooth color (b) relationship of color data taken by nonpolarized (NP), cross‐polarization photography (CP), and spectrophotometry (SP). Materials and methods: Fifty extracted human maxillary incisors were coated with resin on their palatal surfaces. Their color was measured with NP, CP, and SP and their dimensions were scanned by an intraoral scanner. The labial enamel was removed using a modified selective enamel demineralization technique. Tooth dimensions and color were recorded again. The differences in the labial enamel thickness (Δ T ) and color (∆ E *00 and ∆ L *, ∆ a *, ∆ b *) were statistically analyzed with the Pearson correlation coefficient and simple linear regression. Results: In CP and SP methods, ΔT and ∆ E *00 were weakly to moderately positively correlated ( r = .38 and .27). In NP, CP, and SP methods, ∆ T and ∆ b * are weakly positively correlated ( r = .27, .27 and .29). The color data of three measuring methods were highly positively correlated ( r > .8). A linear relationship between ∆ E *00 and ∆ T were found (CP and SP groups). Conclusions: (a) Thicker labial enamel has a greater impact on tooth color. (b) Reducing labial enamel thickness shifts the tooth color toward yellow. (c) Tooth color measured from the three methods were highly correlated. Clinical Significance: Knowing the relationship between enamel thickness and tooth color, a clinician can better predict the stump shade before tooth preparation. Due to the highly correlated measuring outcomes, it is reasonable to combine these three methods during shade matching.